2007
DOI: 10.1021/jf063517o
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 2-Nonanone and Milk Proteins in Aqueous Model Systems

Abstract: Interactions of the model flavor compound 2-nonanone with individual milk proteins, whey protein isolate (WPI), and sodium caseinate in aqueous solutions were investigated. A method to quantify the free 2-nonanone was developed using headspace solid-phase microextraction followed by gas chromatography with flame ionization detection. Binding constants (K) and numbers of binding sites (n) for 2-nonanone on the individual proteins were calculated. The 2-nonanone binding capacities decreased in the order bovine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 27 publications
2
31
0
1
Order By: Relevance
“…Thus, Sahu, Kasoju, and Bora (2008) assessed by fluorescence measurements, a saturation concentration of casein micelles of 17 μΜ for the complete binding of 5 μΜ curcumin in a buffered solution (pH 7.4). The evaluation of 2-nonanone or vanillin affinity to sodium caseinate or individual caseins (Kühn, Zhu, Considine, & Singh, 2007;Li, Grün, & Fernando, 2000) reported a number of binding sites of 0.8-1 for both aroma compounds to sodium caseinate or α s1 -casein, and 0.3 for 2-nonanone to β-casein.…”
Section: Effects Of Uhph On Physico-chemical Characteristics Of Phospmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Sahu, Kasoju, and Bora (2008) assessed by fluorescence measurements, a saturation concentration of casein micelles of 17 μΜ for the complete binding of 5 μΜ curcumin in a buffered solution (pH 7.4). The evaluation of 2-nonanone or vanillin affinity to sodium caseinate or individual caseins (Kühn, Zhu, Considine, & Singh, 2007;Li, Grün, & Fernando, 2000) reported a number of binding sites of 0.8-1 for both aroma compounds to sodium caseinate or α s1 -casein, and 0.3 for 2-nonanone to β-casein.…”
Section: Effects Of Uhph On Physico-chemical Characteristics Of Phospmentioning
confidence: 99%
“…Surface hydrophobicity of casein micelles in skim milk was thus evaluated by Gatti, Risso, and Pires (1995) and Gatti, Risso, and Zerpa (1998) using hydrophobic markers such as 1,8-anilinonaphthalenesulfonate (ANS), 2(p-toluidinyl) naphthalene-6-sulfonate (TNS) or Nile Red, to measure its interaction with casein micelles by fluorescence spectroscopy. Kühn, Zhu, Considine, and Singh (2007) studied the binding of a hydrophobic aroma compound, 2-nonanone (0.1-0.8 mM) to individual α s1 and β caseins, sodium caseinate or whey proteins (0.5-2%, w/v) at pH close to 6.8.…”
Section: Introductionmentioning
confidence: 99%
“…BSA has been widely used in drug delivery studies because of its abundance, low cost, ease of purification, and unusual ligand-binding properties (Elzoghby et al, 2012). Previous studies showed that BSA has the highest binding capacity and considerable surface activity among other individual milk proteins (Singh and Ye, 2009;Kühn and Zhu, 2007;Livney, 2010). Moreover, the interaction between resveratrol and human serum albumin assessed by CD spectroscopy, showed no major alterations at low resveratrol concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a number of works have demonstrated the natural tendency of individual caseins or casein micelles to bind bioactive compounds such as vitamin D (13), the flavor compound 2-nonanone (14), anticancer drugs such as mitoxantrone (15), curcumin (16), docosahexaenoic acid (DHA) (17), tea catechins (18) and β-carotene (19). …”
Section: Introductionmentioning
confidence: 99%